2008
DOI: 10.1007/s00464-008-9790-6
|View full text |Cite
|
Sign up to set email alerts
|

Transparent hood attached to the colonoscope: does it really work for all types of colonoscopes?

Abstract: Transparent hood may be a handy and a cost-effective device for reducing pain and simplifying cecal intubation, especially when using a standard adult colonoscope in routine colonoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 18 publications
4
10
1
Order By: Relevance
“…This finding is in accordance with the literature 5 24 25. However, after 2 weeks, no significant differences in the perceived burden of the procedure were reported.…”
Section: Discussionsupporting
confidence: 93%
“…This finding is in accordance with the literature 5 24 25. However, after 2 weeks, no significant differences in the perceived burden of the procedure were reported.…”
Section: Discussionsupporting
confidence: 93%
“…The transparent cap attached to the tip of the colonoscope has been reported to shorten the cecal intubation time and increase the polyp detection rate, particularly by inexperienced endoscopists, but only limited data are available to confirm these benefits [2, 3]. Our study confirmed shorter cecal intubation times for both experienced and trainee endoscopists.…”
Section: Discussionsupporting
confidence: 79%
“…According to several reports, water immersion prolongs cecal intubation time compared to air insufflation colonoscopy . On the contrary, no study reported a longer intubation time while using the attached cap for air insufflation colonoscopy . In our trial, the cap‐assisted technique was not able to shorten the insertion phase of water immersion colonoscopy significantly ( P = 0.73).…”
Section: Discussioncontrasting
confidence: 70%